2016
DOI: 10.1016/j.jid.2016.06.613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imiquimod on Hair Follicle Stem Cells and Hair Cycle Progression

Abstract: Topical imiquimod (IMQ) application is widely used as a model for psoriasiform-like skin inflammation in mice. Although the effects on the epidermis are well characterized, it is unclear how IMQ affects hair follicles and cycling. Here we investigated how IMQ affects hair follicle stem cells and whether the timing of IMQ application influences the immune infiltrate. Our results show that IMQ application at mid and late telogen activated hair follicle stem cells leading to premature hair cycle entry (anagen), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…does not affect hair follicles (HF), whereas wax stripping results in depletion of HF stem cells leading to anagen entry (Amberg et al, 2016;Paus et al, 1994). The effects of depilation cream have not been carefully investigated yet.…”
Section: Effects Of Depilation Methodsmentioning
confidence: 99%
“…does not affect hair follicles (HF), whereas wax stripping results in depletion of HF stem cells leading to anagen entry (Amberg et al, 2016;Paus et al, 1994). The effects of depilation cream have not been carefully investigated yet.…”
Section: Effects Of Depilation Methodsmentioning
confidence: 99%
“…However, exposure to harsh chemicals also results in a degree of inflammation in the interfollicular epidermis and might induce cytokine/chemokine release characteristic of a wound response. In fact, models of induced skin inflammation with topical imiquimod also promote the telogen‐to‐anagen transition in mice . In the epidermis, there is an increase in DETCs following depilation, in a manner reminiscent of the wound healing process …”
Section: Induced Hair Cyclingmentioning
confidence: 99%
“…Furthermore, Amberg, et al ., found that inflammatory macrophages and dermal resident macrophages have different effects in the hair cycle. They showed that resident macrophages inhibit activation of hair follicle stem cells, preventing the entrance to anagen, while inflammatory infiltrating macrophages promote anagen [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Effective depletion of macrophages was confirmed through Mac1 and F4/80 levels, while depletion of LCs and DCs was confirmed MHC class II in the epidermis and the dermis, respectively. Moreover, topical treatment with imiquimod, a drug that is FDA-approved to treat superficial BCC, results in increased infiltration of macrophages and T cells in mice [2]. In addition, tumor peptide-pulsed intra-dermal Langerhans cell vaccines have been shown to be effective at eliciting immunity against melanoma antigens in Phase I clinical trials in patients with stage III or IV melanoma [58].…”
Section: Introductionmentioning
confidence: 99%